The Definitive Guide to db4o - Paterson, Jim (Apress, 2013)
This book is mainly intended for C# and Java programmers who are writing applications that need to store and retrieve objects. It should be useful for programmers of all skill levels, as db4o is incredibly simple to begin using, but it also has sophisticated features and configurations that will appeal to the more experienced programmer. Further, equal time is devoted to each of these popular languages: it’s not a C# book or a Java book. The vast majority of code examples are given in both languages, so the reader who has a preference for one over the other can easily find the relevant code. The reader who will benefit most from this book is one who knows how to program in his chosen environment, but needs to know enough about db4o to start to use it in that environment. The book doesn’t try to teach C# or Java, or to go into detail about all the possible platforms that these languages and db4o support. It sticks to the main objective, which is to comprehensively describe and demonstrate the db4o API and how to make the most of it. For example, a db4o query returns a list of objects. You can do many things with that list: for example, you could simply print it out, or you could bind its contents to be displayed in one of the many different kinds of user interface controls that are available. The task of this book in this case is to show how to get the right list of objects from the database in the first place.